Effect of carbon nanotube and Zn particles addition on the some mechanical properties and thermal conductivity of unsaturated polyester - Jaffer, H. I. (Iraqi Journal of Physics, 2012)
In this research work a composite material was prepared contains a matrix which is unsaturated polyester resin (UPE) reinforced with carbon nanotube the percentage weight (0.1, 0.2, 0.4.0.5) %, and Zn particle the percentage weight (0.1, 0.2,0.4,0.5)%.All sample were prepared by hand lay-up, process the mechanical tests contains hardness test, wear rate test, and the coefficient of thermal conductivity. The results showed a significant improvement in the properties of overlapping, Article containing carbon nano-tubes and maicroparticles of zinc because of its articles of this characteristics of high quality properties led to an, an increase in the coefficient of the rmalconductivity, and increase the hardness values with increased percentage weight when the wear rate increase with increased the applied load and percentage weight